Bird Use of Northern Alaska Oilfield Rehabilitation Sites - Bentzen, Rebecca; Liebezeit, Joe; Robards, Martin; Streever, Bill; Strindberg, Samantha; Zack, Steve (ARCTIC, 2018)
Breeding bird response to habitat rehabilitation after anthropogenic disturbance has received little attention in the Arctic. The North Slope of Alaska is an important breeding ground for many populations of migratory birds and has also supported major oilfields since the late 1960s. The most obvious impacts of industrial development to nesting birds are direct habitat loss and fragmentation resulting from the construction of infrastructure, along with increased mechanical noise, vehicle traffic, and other forms of anthropogenic disturbance. In response to state and federal requirements, efforts have been made to rehabilitate abandoned portions of the oilfields. We compared bird use at rehabilitation sites and at nearby paired reference sites. Densities of shorebirds and passerines varied between rehabilitation sites and reference sites, but waterfowl densities did not. Specifically, passerine and shorebird densities were higher at reference sites in the early or mid-season and lower at reference sites in the late season. Additionally, birds on rehabilitation sites were primarily observed foraging and resting, while behavior observed on paired reference sites was more diverse and included courtship displays, nesting, and aggression. Further, rehabilitation sites supported significantly fewer nests and fewer species than recorded at reference sites. Our findings suggest that sites 3 to 10 years post rehabilitation do not provide bird habitat comparable to nearby reference sites and, by extension, do not provide shorebird and passerine habitat comparable to that found prior to development. However, rehabilitation sites appear to provide adequate habitat for waterfowl and are important to shorebirds and passerines as foraging areas. Continued monitoring will be needed to establish the long-term suitability of rehabilitation sites, compared to reference sites, as breeding habitat for birds. Dans l’Arctique, la réponse des oiseaux nicheurs à la remise en valeur de l’habitat après des perturbations d’origine ...